2022
DOI: 10.1108/ijoes-06-2021-0120
|View full text |Cite
|
Sign up to set email alerts
|

Developing Islamic sustainable and responsible investment criteria: an overview

Abstract: Purpose The purpose of this study is to explore the necessity for developing Islamic sustainable and responsible investment (i-SRI) criteria based on environmental, social and governance issues. Design/methodology/approach To address the above objective, this study adopted a qualitative method via content document analysis and interviews with experts. Findings Based on the analysis, this study discovered five primary aspects that lead to the necessity for developing i-SRI criteria. First, Malaysia has yet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The existing literature, principles and concepts of ESG principles and Maqasid al-Shariah within Takaful operations are analysed. Through this process, pre-determined themes or measurements based on established theories and frameworks suggested by scholars such as Haji Wahab and Mohamed Naim (2023), Abdullah et al (2023) and others (Agustin et al, 2023;Dirie et al, 2023;Harahap et al, 2023; IMEFM 17,3 Marwan et al, 2020;Shahid et al, 2023) are identified. These themes or measurements serve as a foundation for the conceptual framework.…”
Section: Methodsmentioning
confidence: 99%
“…The existing literature, principles and concepts of ESG principles and Maqasid al-Shariah within Takaful operations are analysed. Through this process, pre-determined themes or measurements based on established theories and frameworks suggested by scholars such as Haji Wahab and Mohamed Naim (2023), Abdullah et al (2023) and others (Agustin et al, 2023;Dirie et al, 2023;Harahap et al, 2023; IMEFM 17,3 Marwan et al, 2020;Shahid et al, 2023) are identified. These themes or measurements serve as a foundation for the conceptual framework.…”
Section: Methodsmentioning
confidence: 99%